2018
DOI: 10.1002/ncp.10205
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis Gravidarum

Abstract: Nausea and vomiting of pregnancy affect the majority of pregnancies, while the most severe version, hyperemesis gravidarum (HG), affects a much smaller subset of women. Despite the prevalence of nausea and vomiting of pregnancy and the severe consequences of HG, the pathophysiology of these conditions is not fully understood. Currently, it is thought that a combination of hormonal factors accounts for their development. Multiple treatments have been described for nausea and vomiting of pregnancy and HG with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 200 publications
(351 reference statements)
1
37
0
29
Order By: Relevance
“…Stigmatizing attitudes may contribute to feelings of shame and guilt that lead them to hide their disorder and avoid help ( 35 ). On the other hand, clinical symptoms during pregnancy may be masked due to a reduction in clinical features or the presence of pregnancy sickness and hyperemesis gravidarum ( 36 ). Nonetheless, it is imperative to reach an early diagnosis in order to prevent long-lasting effects on women of reproductive age and impaired fetal outcomes ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stigmatizing attitudes may contribute to feelings of shame and guilt that lead them to hide their disorder and avoid help ( 35 ). On the other hand, clinical symptoms during pregnancy may be masked due to a reduction in clinical features or the presence of pregnancy sickness and hyperemesis gravidarum ( 36 ). Nonetheless, it is imperative to reach an early diagnosis in order to prevent long-lasting effects on women of reproductive age and impaired fetal outcomes ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory indicators have been associated with many acute or chronic diseases and can be used predictively in the early diagnosis of some diseases, in some cases in the diagnosis and in the follow-up of the treatment or clinical picture [9][10][11][12]. Hyperemesis gravidarum is a clinical manifestation that can develop due to many hormonal, psychosocial or biochemical factors [1,2]. An alteration can be observed in these indicator levels in pregnant women with hyperemesis table [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 90% of pregnant women experience nausea in the early period. It has been reported that nausea during pregnancy is caused by an increase in the level of human chorionic gonadotropin hormone (HCG) [1][2][3]. Hyperemesis gravidarum is a clinical manifestation characterized by increased severity and duration of nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nausea and/or vomiting is a common problem for pregnant women affecting approximately 80% of all pregnant women [1]. Hyperemesis gravidarum (HG), which is a severe form of nausea and/or vomiting, is diagnosed with ketonuria and more than 5% weight loss and occurs in 0.3-3% of all pregnant women [2,3].…”
Section: Introductionmentioning
confidence: 99%